Predictor variables for burnout among nursing professionals - da Silva, Adão Ademir (2018)
The aim of the study was to analyze how occupational commitment and perceived job opportunities (organizational factors), career adaptability and Coping (individual factors) contribute to the prediction of burnout. This quantitative study had a sample of 246 nurses from three hospitals in the south region of Brazil. Data were submitted to stepwise backward multiple regressions using the software SPSS 22. Predictive analysis of all the independent variables with respect to the characterization burnout revealed an R²aj (predictive factor) of 49.5%. The results confirm that the organizational factors trigger burnout. However, it is possible to also see the importance of individual factors that trigger burnout syndrome.There is a need to build an environment that minimizes the predictive variables of burnout.